Nilai-Nilai Moral dalam Film Ar-Rihlah Karya Kobun Shizuno - Anggi Yulia Sari (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This article discusses the concept of morality in the film Ar-Rihlah by Kobun Shizuno, using literary reception theory and content analysis. The film presents moral values that are often understood only through textual or denotative meanings, while the film must be understood through a more profound analytical approach. The purpose of this research is to identify the moral values contained in Ar-Rihlah. The method used in this study is a descriptive qualitative method. The results show that the film contains proactive and courageous moral values, faith, trust, submission, and supplication to God, responsibility and leadership, arrogance and opposition, care and protection, exemplary behavior and the desire to become better, loyalty, solidarity, unity, as well as hatred and arrogance towards the people of Mecca. Ar-Rihlah conveys deep moral messages, both positive and negative. The film not only entertains but also encourages the audience to think and improve themselves to become better.